Peningkatan Hasil Belajar Matematika Melalui Model Pembelajaran Problem Based Learning (PBL) Siswa Kelas I SD Negeri Lowokwaru 3 Malang - Lailatul Khasanah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
This research aims to describtion how the implementation of the Problem Based Learning (PBL) teaching model can improve the learning outcomes of first-grade students in mathematics at an elementary school. The method used in this research is Classroom Action Research (CAR). The average mathematics learning scores of the students were observed, starting from the pre-cycle exam where the average score was 58.6%, with 43.47% or 10 students scoring below the Minimum Mastery Criteria (KKM). After the first cycle, it was observed that the average score of the students increased to 66.8%, with 73.9% of the students achieving the KKM and 26.09% or 6 students scoring below the KKM or not yet achieving it. After the second cycle, the average score of the students further increased to 78.73%, with 91.29% or 21 students achieving the KKM, and 8.70% or 2 students scoring below the KKM or not yet achieving it in mathematics. Based on these results, it can be concluded that the implementation of the Problem Based Learning (PBL) teaching model can improve the learning outcomes of first-grade students at SDN Lowokwaru 3 Malang.